O misterério da taxa de câmbio real chinesa: Algumas raz\~oes que podem explicar a diversidade dos resultados - Emerson Fernandes Marçal (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This paper aims to evaluate what are the main long run determinants of Chinese real exchange rate that have depreciated substantially compared to a basket of currencies. The Chinese government started a process of accumulating foreign reserve in growing speed measured in absolute or relative terms particularly after 2000. The results of this paper suggests that the econometric model traditionally used to estimate the equilibrium real exchange rate is substantially improved by the inclusion of the level of reserve in the model in the Chinese case. This variable seems to help explaining the dynamics of Chinese real exchange rate. The result of the paper creates additional challenges to estimate equilibrium real exchange rate and misalignments due to the fact that not just net foreign asset position is important to the long run exchange rate but also its composition might matter.
Keywords: F4; F30; F31; 330; exchange rate misalignment; effective exchange rate; cointegration